Evaluación de parámetros productivos en codornices (coturnix coturnix) con la inclusión de diferentes niveles de levadura de cerveza en el trópico en la fase de postura - Cabanilla Mendieta, Lady Mishell (2024)
The highest costs of animal production are in feeding and reducing them without affecting their productive behavior is what encourages this research, which was developed in the Coastal Region of Ecuador in the Quail Seed Project promoted by the management. of Research of the Technical University of Babahoyo, had the objective to Evaluate Productive Parameters in quails (Coturnix coturnix) with food diets enriched with different levels of brewer's yeast in the Tropics in the laying phase and determine the profitability of the treatments, were used 72 quails, of which 60 were females and 12 were males, 40 days old with an initial average weight of 108.6g. and will remain for 70 days of study. Distributed in 3 treatments with 3 repetitions, compared to a control treatment, the data obtained were analyzed under a Completely Random Design (DCA), for the differences and separation of means, Tukey was used at the significance levels of (P ≤ 0.05 and P ≤ 0.01). Finally, to determine the profitability of the treatments, the Benefit/Cost Ratio was used, evaluating: Feed consumption (g), Egg production units, Production percentage, Average egg mass (g) Total mass of egg (g). Regarding the variables studied with T3, the best results were obtained Egg production units 260; Average egg mass 13.87g; Total mass 18026g with an average feed consumption of 26.20g; However, T0 was the one that recorded the lowest values with production results of 246 eggs; Egg mass 11.13g; Total egg mass 13727.7 in terms of consumption, this treatment recorded the highest value with 31.87g, which increases its productive expenses. It is worth mentioning that the best Benefit/Cost was recorded with T3: 1.29, becoming a nutritious alternative within quail production.